2009
DOI: 10.1016/j.molcel.2009.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of the PP2A-Shugoshin Interaction

Abstract: SUMMARY Accurate chromosome segregation during mitosis and meiosis depends on shugoshin proteins that prevent precocious dissociation of cohesin from centromeres. Shugoshins associate with PP2A, which is thought to de-phosphorylate cohesin and thereby prevent cleavage by separase during meiosis I. A crystal structure of a complex between a fragment of human Sgo1 and an AB’C PP2A holoenzyme reveals that Sgo1 forms a homodimeric parallel coiled-coil that docks simultaneously onto PP2A’s C and B’ subunits. Sgo1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
267
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(279 citation statements)
references
References 55 publications
12
267
0
Order By: Relevance
“…These results suggested that the detection of array peptide binding to RACK1 might be biased towards cationic and hydrophobic sequences, thus requiring careful validation of any residues implicated in order to eliminate potentially artefactual associations. To this end, we first examined the available crystal structures of the PP2A catalytic subunit and its holoenzyme complexes (PDB: 2NPP, 2NYL, 2NYM [44]; 2IAE [45]; 3DW8 [46]; 3FGA [47]; 4I5N, 4I5L [48] in order to assess whether F69, R70, R214 and Y218 might be accessible in the intact protein and so contribute to a potential RACK1 binding site. This revealed that F69 and R70 are indeed exposed, on a heavily contoured surface proximal to the interface between the PP2A catalytic and scaffolding subunits of the holoenzyme, while R214 and Y218 are similarly surface exposed but on the opposite face of PP2A-C at or near the catalytic centre ( Fig.…”
Section: Rack1 and Pp2a-c Complex Was Confirmed (Fig 1a (I) And (Ii))mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that the detection of array peptide binding to RACK1 might be biased towards cationic and hydrophobic sequences, thus requiring careful validation of any residues implicated in order to eliminate potentially artefactual associations. To this end, we first examined the available crystal structures of the PP2A catalytic subunit and its holoenzyme complexes (PDB: 2NPP, 2NYL, 2NYM [44]; 2IAE [45]; 3DW8 [46]; 3FGA [47]; 4I5N, 4I5L [48] in order to assess whether F69, R70, R214 and Y218 might be accessible in the intact protein and so contribute to a potential RACK1 binding site. This revealed that F69 and R70 are indeed exposed, on a heavily contoured surface proximal to the interface between the PP2A catalytic and scaffolding subunits of the holoenzyme, while R214 and Y218 are similarly surface exposed but on the opposite face of PP2A-C at or near the catalytic centre ( Fig.…”
Section: Rack1 and Pp2a-c Complex Was Confirmed (Fig 1a (I) And (Ii))mentioning
confidence: 99%
“…Y218 is located quite close to the catalytic pocket and interestingly, in one crystal structure (PDB: 3FGA [47]), Y218 forms part of the surface contact for a helical fragment derived from the shugoshin protein, Sgo1, which facilitates recruitment of PP2A to centromeric cohesion [47,55] . Although it is not thought that the interaction between RACK1 and PP2A mimics this interaction precisely (because RACK1 is unlikely to reorganise so as to present a helical motif), the observed complex between PP2A-C and Sgo1 does establish a precedent for Y218 as part of a binding surface for a partner protein.…”
Section: Rack1 and Pp2a-c Complex Was Confirmed (Fig 1a (I) And (Ii))mentioning
confidence: 99%
“…12,13,18,19 During meiosis Cdc55 regulates sister chromatid separation through shugoshin-dependent separase regulation. 32,43 The results presented lead us to conclude PP2A Cdc55 regulates other events during meiosis, as well. Meiotic entry, premeiotic DNA replication and DSB formation were accelerated due to loss of CDC55, suggesting a shortening of meiotic S phase.…”
Section: Cdc55 Cdc28mentioning
confidence: 69%
“…32,39,[43][44][45] Here we asked if total loss of yeast PP2A function causes defects in meiosis I. Our results indicate PP2A…”
Section: Introductionmentioning
confidence: 90%
“…Recruitment of PP2A Rts1 to the kinetochores is achieved by its physical interaction with Sgo1 and a mutant form of Sgo1 that fails to bind to PP2A Rts1 is defective in protection of centromeric cohesion [73]. PP2A Rts1 opposes phosphorylation of meiotic cohesin subunit Rec8 at the centromeres by Hrr25, a casein kinase-1 and the Dbf4-dependent kinase Cdc7 [74].…”
Section: Iii) Protection Of Centromeric Cohesionmentioning
confidence: 99%